CISSP - Gregg, Michael (Michael C.) (Exam cram 2., 2006)
A new edition of this title is available, ISBN-10: 0789738066 ISBN-13: 9780789738066 Learn what you need to know to master the CISSP security technology and the certification exam with the CISSP Exam Cram 2. A perfect compliment to larger study guides, the CISSP Exam Cram 2 is a great way to find out exactly what will be expected of you during the real exam. The book includes: Exam topic-focused chapters. Practice questions at the end of each chapter. Exam Alerts that highlight key terms and areas. Two full-length practice exams. An electronic test engine provided by MeasureUp on CD-ROM with additional practice exams. The "Cram Sheet" tearcard for last minute exam review. Prepare for the CISSP certification exam with the proven Exam Cram 2 learning tools provided in the CISSP Exam Cram 2.